How does quality-dominant logic ensure marketing analytics success and tackle business failure in industrial markets? - Akter, Shahriar; Hossain, Md Afnan; Tarba, Shlomo Y.; Leonidou, Erasmia (My University, 2023)
Despite the burgeoning research on business failure in industrial markets, not much has been conducted on the role played by marketing analytics in mitigating such failure in the post-pandemic period. Against this backdrop, this study was aimed at investigating the antecedents of marketing analytics success (MAS) and its overall effects on strategic business value and profitability. Drawing on quality-dominant logic through the dynamic capability lens, this study yielded a model that, on the basis of data, model, and deployment quality, explains the achievement of MAS and the avoidance of business failure. This study, the data for which were gathered in Australia from 314 sample elements, shows that MAS significantly contributes to strategic business value and profitability. Such findings present a theoretically rigorous and practically relevant framework of MAS capable of mitigating the causes of business failure by harnessing analytics insights.
Keywords: Business failures; Marketing analytics; Marketing analytics success; Profitability; Strategic business value